Enhancement of lipid accumulation in Monoraphidium sp. QLY-1 by induction of strigolactone. (September 2019) - Song, Xueting; Zhao, Yongteng; Li, Tao; Han, Benyong; Zhao, Peng; Xu, Jun-Wei; Yu, Xuya
Highlights: Strigolactone (SL) significantly increased the lipid productivity of alga. SL triggered an increase in the levels of cytosolic Ca 2+ and nitric oxide (NO). Ca 2+ prompted biomass and lipid productivity in alga under SL induction. Ca 2+ regulated NO signalling in alga in response to SL induction. Abstract: In this study, the effects of strigolactone (SL) on the biomass, lipid content, biochemical properties, and gene transcription of Monoraphidium sp. QLY-1 were examined. The lipid content and lipid productivity increased by 61% and 55% in QLY-1 under 1 μM SL induction compared to the control group, respectively. SL also upregulated the levels of endogenous NO and Ca 2+ and lipid biosynthesis gene transcription. Subsequently, the relationship between Ca 2+ and nitric oxide (NO) in the regulation of cell growth and lipid accumulation of QLY-1 under SL induction conditions was analysed. An increase in endogenous Ca 2+ regulated cell growth and lipid biosynthesis by modulating the levels of NO and lipid biosynthesis-related gene expression. Collectively, this study provided a valuable approach for biofuel production from microalgae under SL induction and demonstrated that there is crucial crosstalk between the Ca 2+ and NO signalling in the manipulation of lipid biosynthesis in microalgae under SL treatment.